Fully Automated Measurement of Cochlear Duct Length From Clinical Temporal Bone Computed Tomography. Issue 2 (18th September 2021) - Neves, Caio A.; Tran, Emma D.; Cooperman, Shayna P.; Blevins, Nikolas H.
Abstract : Objectives/Hypothesis: To present and validate a novel fully automated method to measure cochlear dimensions, including cochlear duct length (CDL). Study Design: Cross‐sectional study. Methods: The computational method combined 1) a deep learning (DL) algorithm to segment the cochlea and otic capsule and 2) geometric analysis to measure anti‐modiolar distances from the round window to the apex. The algorithm was trained using 165 manually segmented clinical computed tomography (CT). A Testing group of 159 CTs were then measured for cochlear diameter and width ( A ‐ and B ‐values) and CDL using the automated system and compared against manual measurements. The results were also compared with existing approaches and historical data. In addition, pre‐ and post‐implantation scans from 27 cochlear implant recipients were studied to compare predicted versus actual array insertion depth. Results: Measurements were successfully obtained in 98.1% of scans. The mean CDL to 900° was 35.52 mm (SD, 2.06; range, [30.91–40.50]), the mean A ‐value was 8.88 mm (0.47; [7.67–10.49]), and mean B ‐value was 6.38 mm (0.42; [5.16–7.38]). The R 2 fit of the automated to manual measurements was 0.87 for A ‐value, 0.70 for B ‐value, and 0.71 for CDL. For anti‐modiolar arrays, the distance between the imaged and predicted array tip location was 0.57 mm (1.25; [0.13–5.28]). Conclusion: Our method provides a fully automated means of cochlear analysis from clinical CTs. The distribution of CDL, dimensions, and cochlear quadrant lengths is similar to those from historical data. This approach requires no radiographic experience and is free from user‐related variation. Level of Evidence: 3 Laryngoscope, 132:449–458, 2022